New Material of Carbonaceous Compressions from the ∼1.5 Ga Singhora Group, Chhattisgarh Supergroup, India, and their Interpretation as Benthic Algae - Singh, Veeru Kant; Sharma, Mukund (Frontiers in Earth Science, 2022)
The origin, antiquity, and affinity of benthic seaweeds (multicellular algae) in the geological past are shrouded in a mystery due to their preservation bias. In this paper, we present a new material of well-preserved carbonaceous compression fossils in shale horizons of the Mesoproterozoic (ca. ~1500 – 1300 Ma) Singhora Group of the Chhattisgarh Supergroup. Eleven distinct taxa, including one new taxon Palaeoscytosiphon shuklaii n. gen. et. sp., and one new species Jiuqunaoella sergeevii n. sp. are established. Also, four unidentified morphologies are reported. Morphologically, the carbonaceous fossils are fan-shaped, palmate, elongated, leaf-like algal thallus with/without holdfast at the base, isolated or dichotomously branched long filaments, along with multicellular reproductive structures. Results of Laser Raman Spectroscopy and Energy-dispersive X-ray spectroscopy (EDX) are also presented in support of the biogenicity. Collectively, the preservation mode of the Singhora carbonaceous fossils suggests multicellular algal affinity and also adds to a Burges Shale-type (BST) taphonomic window in the Pre-Ediacaran biosphere.